2012
DOI: 10.1186/1471-2121-13-15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mitosis regulators through data mining with human centromere/kinetochore proteins as group queries

Abstract: BackgroundProteins functioning in the same biological pathway tend to be transcriptionally co-regulated or form protein-protein interactions (PPI). Multiple spatially and temporally regulated events are coordinated during mitosis to achieve faithful chromosome segregation. The molecular players participating in mitosis regulation are still being unravelled experimentally or using in silico methods.ResultsAn extensive literature review has led to a compilation of 196 human centromere/kinetochore proteins, all w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 90 publications
11
59
0
Order By: Relevance
“…[17][18][19]. It has been reported that the AAA-ATPase TRIP13 is a kinetochoreassociated protein that binds to p31 comet (16). Because the Cdc20-Mad2 substrate used in our assay contained p31 comet (necessary for the release of the subcomplex from MCC), TRIP13 seemed to be a likely candidate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[17][18][19]. It has been reported that the AAA-ATPase TRIP13 is a kinetochoreassociated protein that binds to p31 comet (16). Because the Cdc20-Mad2 substrate used in our assay contained p31 comet (necessary for the release of the subcomplex from MCC), TRIP13 seemed to be a likely candidate.…”
Section: Resultsmentioning
confidence: 99%
“…The Mad2-binding protein p31 comet has important roles in checkpoint inactivation (11,12,14,(20)(21)(22) and MCC disassembly (10,21), and has been reported to bind to TRIP13 (16). We therefore examined whether the actions of TRIP13 described above require the participation of p31 comet .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations